1999
DOI: 10.1159/000024030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin–3, Interleukin 5 and Hyaluronic Acid on Cultured Eosinophils Derived from Human Umbilical Cord Blood Mononuclear Cells

Abstract: Background: Several studies have shown that cultured eosinophils can be generated from human umbilical cord blood mononuclear cells (UCMC) in the presence of interleukin (IL)–3 and IL–5 in vitro. Other reports have indicated that cellular adhesion to hyaluronic acid (HA) enhances the proliferation of cultured eosinophils derived from CD34+ cells purified from UCMC. The aim of this study was to obtain large numbers of mature eosinophils from UCMC using IL–3, IL–5 and HA, and to investigate their functions. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Even after 35 to 42 days of culture, when >95% of the cells expressed characteristic eosinophil morphology, the intracellular concentrations of EDN were lower (700-1600 ng/1 3 10 6 cells) than the concentrations observed in any of our groups. 23 Further culture of the developing cells resulted in a profound loss of EDN content. In contrast, Al-Rabia et al 24 reported expression of major basic protein and ECP by 15% to 20% of cultured peripheral blood CD34 + stem cells incubated with stem cell factor, FLT1 ligand, IL-3, and IL-5 for 3 to 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Even after 35 to 42 days of culture, when >95% of the cells expressed characteristic eosinophil morphology, the intracellular concentrations of EDN were lower (700-1600 ng/1 3 10 6 cells) than the concentrations observed in any of our groups. 23 Further culture of the developing cells resulted in a profound loss of EDN content. In contrast, Al-Rabia et al 24 reported expression of major basic protein and ECP by 15% to 20% of cultured peripheral blood CD34 + stem cells incubated with stem cell factor, FLT1 ligand, IL-3, and IL-5 for 3 to 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…The chemotaxis assay was performed using a 24-well microchemotaxis chamber as described previously with minor modifications (26). In brief, chemoattractants were diluted in RPMI 1640 medium supplemented with 1 mg/ ml BSA and placed in the lower wells (250 μ l/well).…”
Section: Migration Assaymentioning
confidence: 99%
“…Dyer et al (2008), alternatively, described a series of culture conditions in which the addition of stem cell factor (SCF), FLT3-ligand, and IL-5 induced differentiation of mouse bone marrow progenitor cells into eosinophils. Human progenitor cells from the umbilical cord (Ten et al, 1991; Ohashi et al, 1999) and bone marrow (Clutterbuck et al, 1989) have also been successfully differentiated into eosinophils in vitro in the presence of IL-3 and IL-5. While these are viable options to obtain human bone marrow-derived eosinophils, it may not represent the best option as the differentiation of these cells from progenitor populations can be labor and/or time intensive (2–4 weeks) as well as costly.…”
Section: Introductionmentioning
confidence: 99%